Study of Radon Radiation in the Area of the Akchatau Polymetallic Mine, Republic of Kazakhstan - Yuriy Pak; Dmitriy Pak; Vladimir Matonin; Diana Ibragimova; Pavel Timoshenko; Yuriy Barkov; Anar Tebayeva; Pavel Medvedev (Atmosphere, 2025)
The data on the volumetric radon activity of the Akchatau territory were systematized in the context of radioecological safety. Radon (Rn222 and Rn220) and indoor radon (isotopes Po, Pb, and Bi) make a significant contribution to radon radiation in residential and industrial premises. Increased radon concentration in a number of areas is associated with the Akchatau tungsten–molybdenum mine. The source of radon in geological terms is acid leucocratic granites in the northwestern and southeastern parts of the studied territory. Seasonal assessment of radon radiation was carried out using modern devices “Alfarad Plus” and “Ramon-Radon”. Frequency analysis of the average annual equivalent equilibrium concentration (EEC) in 181 premises showed that only in 47.5% of the premises does the volumetric radon activity not exceed the current standards (200 Bq/m3). Differentiated values of radon concentration were obtained in cases where daily and seasonal observations were carried out. In 43.1% of premises, the effective dose varies from 6.6 mSv/year to 33 mSv/year, and for 9.4% of premises, from 33 mSv/year to 680 mSv/year. The increased radon concentration is caused by high exhalation from the soil surface, the radioactivity of building materials, and low air exchange in the surveyed premises. In the northwestern part of Akchatau, anomalous zones were found where the exposure dose rate of gamma radiation exceeds 0.6 mkSv/hour. An objective assessment of radon largely depends on a number of factors that take into account the geological, technical, atmospheric, and climatic conditions of the region. Therefore, when planning an optimal radon rehabilitation strategy, it is necessary to take the following factors into account: the design features of residential premises and socio-economic conditions. Practical recommendations are given for radiation-ecological and hygienic monitoring of radon safety levels in the environment to reduce effective doses on the population.